2009
DOI: 10.1111/j.1468-2494.2009.00531_5.x
|View full text |Cite
|
Sign up to set email alerts
|

DPPH free‐radical scavenging ability, total phenolic content, and chemical composition analysis of forty‐five kinds of essential oils

Abstract: A long-term usage investigation of a scalp lotion containing Eucalyptus extract, which increases the amount of ceramide in the skin, was carried out to explore the change in physical properties of the hair fiber. Half-head or whole-head usage studies of a scalp lotion with Eucalyptus extract were carried out for the following groups: Japanese female, Japanese senior female, Japanese male, and Caucasian female panelists. As a result, the improvement in hair luster and bounce in the root part of the hair were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…(), Wang et al . () and Gülçin et al . () also demonstrated that clove bud EO had high phenolic content compared with other EOs like thyme EOs (Gülçin et al .…”
Section: Resultsmentioning
confidence: 91%
“…(), Wang et al . () and Gülçin et al . () also demonstrated that clove bud EO had high phenolic content compared with other EOs like thyme EOs (Gülçin et al .…”
Section: Resultsmentioning
confidence: 91%
“…[7] It was also found that one-half millilitre of cinnamon leaf has free radical scavenging ability with an EC50 of 53 µ/ml and has a total phenolic content of 420 mg/g as the major chemical composition. [8] Hepatoprotective Activity The extract of C. cassia has been reported to have better hepatoprotective activity against alcohol and carbon tetrachloride induced hepatic injury. Its hepatoprotective property may be due to its free radical scavenging activity.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…DPPH radical scavenging activity was evaluated using the following method from a previous study (Wang, Wang, & Yih, 2008). Twenty microliters of ABE solution were mixed with 180 μL of diphenylp-picrylhydrazyl radical (DPPH) in ethanol and 20 μL of different concentrations of sample and then incubated for 20 min at room temperature with light protection.…”
Section: Dpphradicalscavengingassaymentioning
confidence: 99%